Right to Information : Recent Spread of RTI Legislation - Mendel, Toby (World Bank, Washington, DC, 2015)
In the last 20 years, there has been a massive growth in the number of national laws giving individuals the right to access information held by public bodies (right to information or RTI laws). The number of countries with such laws has grown from 19 mostly Western democracies i